A relação entre aprendizagem organizacional, inovação e cultura organizacional - Ferreira, Marcos Antonio (2018)
Knowledge as an economic asset, capable of generating value for the organization, has taken on importance in literature and has been studied in academia since then. With this change, new questions have been formulated. Theoretical models were developed to identify how this knowledge could be converted into competitive advantage, and also on the role of organizational culture in the creation of knowledge, by authors such as Senge (1990). Subsequently, the relation between learning and innovation of Nonaka and Takeuchi (1995) evidences an opportunity of studies to establish these effects empirically. On the other hand, from the theoretical model of Cameron and Quinn (2006) and the Quinn Typology, as presented in Santos (2000), one can refine these relations of the effects of organizational culture on organizational learning and innovation, outlining the effect of culture by its subtypes: group, innovative, hierarchical and rational. Therefore, the objective of this work is to verify the effects of cultural subtypes on organizational learning and its effect on innovation. Then, to verify if the organizational culture, through its subtypes, has effect on innovation. Given that a range of resources is demanded by organizations aiming at the fulfillment of their mission, having a good team and the necessary technologies were considered in the past as sufficient elements to keep an organization profitable and competitive. However, research conducted on different continents, countries and industries showed that only the strategy of providing the team with the structural conditions, skills for teamwork and technical expertise, and strengthening the necessary capabilities were not enough to generate strategic potential, capture opportunities and improve innovative capacity. Given the objectives of this work, the hypotheses to be tested relate to the relationship between organizational learning and innovation, organizational culture and learning and also innovation. Following Sanz-Valle et al. (2011) and based on the theory outlined by Hair Jr. et al. (2006), the analysis will be constructed in two stages: first the confirmatory factorial analysis is done to validate the instruments and then the structural equations modeling is used to test the hypotheses proposed. A research instrument was used to collect data on the perception of collaborators about their organizations. This instrument returned 168 responses and approximately 90 of these were valid for the quantitative study. From the modeling of structural equations it was observed that there is a positive and statistically significant effect of group culture in organizational learning, and statistically significant effects, however, inconclusive effects of learning in innovation, and of group culture in innovation